“Kelangensih”: Karya Musik Inovatif Perpaduan Alap Bali dan Alap Hindustani - Desak Made Suarti Laksmi; I Ketut Sumerjana; I Komang Darmayuda; Jyothi Devi Krishnanandayani (Institut Seni Indonesia Denpasar, 2023)
Pupose: Traditional Balinese vocal karawitan has a rich variety of types and variants. It also has a function and purpose that is deeply rooted as a treasure of musical art which is firmly bound by its standards. Many efforts have been made to develop it both in its integration with instrumental music and with Western musical instruments in various genres. Research methods: Several stages of creation methods such as exploration, improvisation, formation and evaluation are a creation process that produces an innovative musical work